Centers of Gravity: Regional Powers, Democracy, and Trade. Issue 2 (4th March 2017) - Peterson, Timothy M.; Lassi, Thomas
ABSTRACT: Classic studies on hegemonic stability and power transition suggest that concentration of capabilities favoring a single state can promote economic cooperation and discourage militarized conflict. However, tests of these arguments have been primarily limited to examining temporal variation in global capability distributions and corresponding levels of system-wide cooperation; few have examined the impact of capability concentration at the region level. In this article, we contend that concentration of regional military capabilities corresponds to lower trade costs for states throughout a region and to an incentive for weaker states to de-prioritize expenditure on the military, freeing resources that can be used to promote trade. As a result, this condition promotes higher levels of trade, particularly within the region. We also argue that democratic regional powers are better able to foster confidence in the sustainability of cooperation; thus, the trade-enhancing impact of concentrated regional capabilities is stronger when the predominant state is more democratic. We find evidence in support of our expectations in statistical models examining state trade between 1960 and 2007.